SIMPLIFYING LAPAROSCOPIC HERNIOTOMY IN CHILDREN - A PROSPECTIVE COMPARATIVE STUDY OF CONVENTIONAL LAPAROSCOPY AND INSTRUMENTATION WITH STAB INCISION - M Srinivas Rao,; Edamakanti Swetha Soni,; Mayur Shyam Soni, (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: Paediatric inguinal hernias (IHs) are common. The first paediatric laparoscopic hernia repair was described by El-Gohary and colleagues in the United Arab Emirates in 1993. Inguinal hernias (IHs) are common in the paediatric population with a reported incidence ranging from 3 to 5% in term infants and up to 13% in infants born before 33 weeks of gestation. In India, inguinal hernia repair is a frequently performed surgical procedure due to its high occurrence rate and the availability of various effective treatment methods.Aim and Objective: A study insimplifying laparoscopic herniotomy in children - a prospective comparative study of conventional laparoscopy with trocar cannulas and instrumentation with stab incision without trocar cannulas to study feasibility of performing laparoscopic procedures without using cannulas for introducing instruments.Material and Methods: This was a prospective comparative study carried out in the Department of Pediatrics Surgery for a period of 18 months i.e, January 2023 to July 2024, where the first 30 laparoscopic herniotomies were done using 3 port technique. Next 30 laparoscopic herniotomies are done using simple stab incisions to introduce laparoscopic instruments into abdomen. 5 mm Camera port with 30 degree laparoscope is introduced transumbilically in both groups. We conducted the study in lap herniotomy because this condition is common and procedure is short for measuring the variables. We routinely note the surgical time in all procedures as protocol, which we copied from our OT register for comparison. We compared all the complications as outcomes.Results: In the present  study we observed  that the maximum number of patients were present in the age group 2-3 years of age followed by the age group 4-5 years in both groups. In the present study among a total 60 patients , maximum numbers of patients were male than female respectively. In our study three individuals experienced scrotal edema in one group other two individual in another group. Temporary hydroceles, lasting only a few days, were found in one individual in each group. Operative time is short and analgesic requirement is minimal in stab incision group.Conclusion: Laparoscopic procedures can be performed effectively and safely with stab incisions for instrument access. There is significant cost savings related to the elimination of utilisation of cannulas. We believe that use of stab incisions for instrument access is equivalent to the traditional cannula approach and should be considered whenever possible.